2016
DOI: 10.17957/tpmj/16.3322
|View full text |Cite
|
Sign up to set email alerts
|

Obesity; Association of Serum Vitamin D Levels

Abstract: Article Citation: Rani K, Memon AR, Akram M, Memon PJ. Obesity; association of serum vitamin d levels. Professional Med J 2016;23(6):665-668.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…According to our results, obese women were relatively more vitamin D deficient as compared to normal women. This is in accordance to two small studies carried out in local obese women [ 19 , 20 ]. These studies have used 20 ng/ml as the cutoff limit to define vitamin D deficiency, but we have used the latest cutoff level (12 ng/ml) for this purpose [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our results, obese women were relatively more vitamin D deficient as compared to normal women. This is in accordance to two small studies carried out in local obese women [ 19 , 20 ]. These studies have used 20 ng/ml as the cutoff limit to define vitamin D deficiency, but we have used the latest cutoff level (12 ng/ml) for this purpose [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…These studies have used 20 ng/ml as the cutoff limit to define vitamin D deficiency, but we have used the latest cutoff level (12 ng/ml) for this purpose [ 18 ]. In spite of the relatively lower cutoff value, our percentage of vitamin D-deficient obese women (40.7%) was comparable to that of one of the above mentioned studies, i.e., 40% [ 19 ]. As a consequence of relatively more vitamin D deficiency in obese women, the mean PTH concentration was significantly higher than in nonobese women (20.8 ± 15.9 versus 17.1 ± 12.7, respectively, P = 0.0034), but the mean serum calcium level was comparable in both groups.…”
Section: Discussionsupporting
confidence: 77%
“…These results matched a study carried out in Karachi where they found that 40% of obese patients were having hypovitaminosis D, but differed from our study in that they did not take diabetes into account. 19 Similarly, prevalence of hypovitaminosis D was found to be about 81% in Spanish obese children. 20 In summary, our study provided enough evidence for a possible association of hypovitaminosis D with poor glycemic control and obesity in type II diabetic patients, but large interventional studies implying vitamin d supplementation are needed to confirm our results.…”
Section: Although Vitamin D Deficiency Has Been Linkedmentioning
confidence: 96%